A better understanding of the polymeric irradiation using physico-electrochemical characteristics. Issue 11 (2nd December 2021) - El-Raheem, Hany Abd; Hassan, Rabeay Y. A.; Khaled, Rehab; El-Dek, S.I.; Farghali, Ahmed; El-Sherbiny, Ibrahim M.
Abstract : Poly(ester-urethane) urea (PEUU) based on ethanolamine as a chain extender contain hydroxyl and amino groups was chemically synthesized using 1, 1'-methylenebis(4-isocyanatobenzene) MDI diisocyanates, and castor oil. One step polymerization procedure has been used to complete the PEUU formation and this polymeric target was irradiated with different doses (100, 250, 400, and 600 kGy) of gamma rays. A full physico-electrochemical characterization package was performed on the solid surfaces, radiated vs. non-irradiated, for a better understanding of the structure changes. To that end, Fourier transform infrared spectroscopy (FTIR), and the morphological features were characterized by the scanning electron microscope (SEM). Thermal stability was investigated using differential scanning calorimetry (DSC), while the crystallinity and electrochemical properties were explored by the X-ray diﬀraction (XRD), and cyclic voltammetry (CV), respectively. Eventually, swelling, crosslinking density, mechanical strength, water absorption, and contact angle measurements were discussed. Ultimately, the crosslinking density was discovered to be irradiated dependent. Worth mentioning here, this kind of study is recommended as a protocol that could be applied on other polymeric targets exposed to electromagnetic radiations.